Y+26=3y-12

Simple and best practice solution for Y+26=3y-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y+26=3y-12 equation:


Simplifying
Y + 26 = 3y + -12

Reorder the terms:
26 + Y = 3y + -12

Reorder the terms:
26 + Y = -12 + 3y

Solving
26 + Y = -12 + 3y

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + Y = -12 + -26 + 3y

Combine like terms: 26 + -26 = 0
0 + Y = -12 + -26 + 3y
Y = -12 + -26 + 3y

Combine like terms: -12 + -26 = -38
Y = -38 + 3y

Simplifying
Y = -38 + 3y

See similar equations:

| 5(3m-4)+7m=156 | | -8(x-1)=24 | | 3.5x-0.6875=x+0.25 | | -3(-5n+2)=5[-3n+3(-n-3)] | | 6x+11=4x-18 | | -6(b-5)+2=15-(b+3) | | 24x^3(y+6)+48x^2(y+6)-16x(y+6)= | | x-4x-5=6x+15 | | 3x+3=48-2x-10 | | 2.5d+6.25=1+3.25d | | (2x+3y)=3x-y | | P=100-0.05Q | | 8(4-6n)-2n=282 | | 4y^3+3y^2-8y-6= | | 75=50+15x+(x)(x) | | x^2+124+49=1000 | | 16x^2-48x-64=0 | | -3(6y-6)-y=-3(y-2) | | -1=7-2(7p+3) | | 6x-2=6(x-1)+11 | | 3x-7=2(x-1)+5 | | 3(x+7)-3=63-2x | | -90=8-2(7n-7) | | 6t^2-19t-20= | | 3(1.2)2= | | y+96=5y | | 6(-6m+8)=-96 | | X-8=48-15(x+8) | | (3)(10)n=(4)(5) | | 2s^6+11s^3t+12t^2= | | 6x+4=-28 | | 0.08x-0.12(x-4)=0.03(x-5) |

Equations solver categories